Optimal combination of arsenic trioxide and copper ions to prevent autoimmunity in a murine HOCl-induced model of systemic sclerosis - Chêne, Charlotte; Rongvaux-Gaïda, Dominique; Thomas, Marine; Rieger, François; Nicco, Carole; Batteux, Frédéric (Frontiers in Immunology, 2023)
Systemic sclerosis (SSc) is a rare chronic autoimmune disease characterized by diffuse fibrosis of the skin and internal organs and vascular abnormalities. The etiology and physiopathology are complex due to the heterogeneity of its overall clinical presentation. Arsenic trioxide (ATO) has been proven to be effective against SSc, sclerodermatous Graft-versus-Host Disease, multiple sclerosis, Crohn’s disease or systemic lupus erythematosus animal models and has demonstrated promising effects in human clinical trials. Its efficacy was shown to be related at least in part to the generation of Reactive Oxygen Species (ROS) and the selective deletion of activated immune cells and fibroblasts. However, ATO can induce some adverse effects that must be considered, especially when used for the treatment of a chronic disease. We evaluate here, in a mouse model of SSc, the improved efficacy of ATO when associated with a Fenton-like divalent cation, namely copper chloride (CuCl2), also known to trigger the production of ROS. In preliminary experiments in vitro, ATO 1 µM + CuCl2 0.5 µM increased ROS production and increased apoptosis of NIH 3T3 murine fibroblasts compared to 1 µM ATO alone. In vivo, in the HOCl-induced mouse model of SSc, co-treatment with ATO 2.5 μg/g + CuCl2 0.5 μg/g significantly alleviated clinical signs such as the thickening of the skin (p<0.01) and cutaneous fibrosis, in a manner equivalent to treatment with ATO 5 µg/g. Our results provide evidence that co-treatment with ATO 2.5 μg/g + CuCl2 0.5 μg/g decreases the number of B cells and the activation of CD4+ T lymphocytes. The co-treatment substantially blocks the NRF2 signaling pathway, increases H2O2 production and results in the improvement of the health status of mice with experimental SSc. In conclusion, copper combined with ATO treatment halved the concentration of ATO needed to obtain the same effect as a high dose of ATO alone for the treatment of SSc mice. The strategy of using lower doses of drugs with different mechanisms of action in combination has many potential advantages, the first being to lessen the potential side effects induced by ATO, a drug with side effects quickly increased with dosage.